2017
DOI: 10.1002/adfm.201704433
|View full text |Cite
|
Sign up to set email alerts
|

Novel Eco‐Friendly Starch Paper for Use in Flexible, Transparent, and Disposable Organic Electronics

Abstract: An eco-friendly biodegradable starch paper is introduced for use in nextgeneration disposable organic electronics without the need for a planarizing layer. The starch papers are formed by starch gelatinization using a very small amount of 0.5 wt% polyvinyl alcohol (PVA), a polymer that bound to the starch, and 5 wt% of a crosslinker that bound to the PVA to improve mechanical properties. This process minimizes the additions of synthetic materials. The resultant starch paper provides a remarkable mechanical str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(43 citation statements)
references
References 55 publications
1
42
0
Order By: Relevance
“…In 2018, Jeong et al reported on the preparation of thin, smooth and optically transparent substrates by gelatinization of potato starch (blended with a small amount of chemically crosslinked polyvinyl alcohol to enhance the mechanical properties) and on the fabrication of bottom-gate, top-contact TFTs on these substrates. 44 The authors used a vapor-deposited parylene layer with a thickness of 870 nm as the gate dielectric and evaluated three All TFT layers (source/drain contacts, semiconductor, gate dielectric, gate electrodes) were deposited by inkjet printing. Reprinted with permission.…”
Section: Organic Transistors On Nanocellulose Supercalendered and Spmentioning
confidence: 99%
“…In 2018, Jeong et al reported on the preparation of thin, smooth and optically transparent substrates by gelatinization of potato starch (blended with a small amount of chemically crosslinked polyvinyl alcohol to enhance the mechanical properties) and on the fabrication of bottom-gate, top-contact TFTs on these substrates. 44 The authors used a vapor-deposited parylene layer with a thickness of 870 nm as the gate dielectric and evaluated three All TFT layers (source/drain contacts, semiconductor, gate dielectric, gate electrodes) were deposited by inkjet printing. Reprinted with permission.…”
Section: Organic Transistors On Nanocellulose Supercalendered and Spmentioning
confidence: 99%
“…Organic TFTs have been successfully fabricated on various types of paper, including commercial packaging paper, printing paper, photo paper, homemade paper, starch paper, and banknotes . In some cases, one or several coatings were applied to the surface of the paper prior to TFT fabrication in order to smoothen or seal the surface .…”
Section: Introductionmentioning
confidence: 99%
“…As people expected, the processability, performance, and stability of electronic materials are basic characteristics of paper electronics which demand that paper‐based circuits must have controllable scale, low resistance and high stability under deformation. Although most paper electronics are disposable, the circuits on paper will also raise environmental concern as they cannot be degraded or recycled like their substrate paper . Burning is the popular method to recycle functional materials such as silver nanoparticles on paper, it will be detrimental to environment and functional materials which are also difficult to be separated from the debris of paper.…”
Section: Introductionmentioning
confidence: 99%